2007
DOI: 10.1002/hyp.6720
|View full text |Cite
|
Sign up to set email alerts
|

Enhancements to, and forthcoming developments in the Interactive Multisensor Snow and Ice Mapping System (IMS)

Abstract: Abstract:The National Oceanic and Atmospheric Administration's National Environmental Satellite Data and Information Service (NOAA/NESDIS) Interactive Multisensor Snow and Ice Mapping System (IMS) has undergone substantial changes since its inception in 1997. These changes include the data sources used to generate the product, methodology of product creation, and even changes in the output. Among the most notable of the past upgrades to the IMS are a 4-km resolution grid output, ingest of an automated snow det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
258
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 325 publications
(261 citation statements)
references
References 25 publications
2
258
0
1
Order By: Relevance
“…Brown and Derksen (2013 found that the increasing trend (reported by Cohen et al 2012a) is only present in a single satellite-based data set, being an artificial one due to an improved snow mapping over the years (Helfrich et al 2007). Brown and Derksen (2013) noted, however, that there is evidence of increasing precipitation and winter snow accumulation over large regions of Russia (Bulygina et al 2009;Borzenkova and Shmakin 2012;Callaghan et al 2011;Park et al 2012), which is consistent with increased air moisture over the Arctic Ocean and Eurasia Cohen et al 2012a).…”
Section: Changes In Terrestrial Snow Packmentioning
confidence: 99%
“…Brown and Derksen (2013 found that the increasing trend (reported by Cohen et al 2012a) is only present in a single satellite-based data set, being an artificial one due to an improved snow mapping over the years (Helfrich et al 2007). Brown and Derksen (2013) noted, however, that there is evidence of increasing precipitation and winter snow accumulation over large regions of Russia (Bulygina et al 2009;Borzenkova and Shmakin 2012;Callaghan et al 2011;Park et al 2012), which is consistent with increased air moisture over the Arctic Ocean and Eurasia Cohen et al 2012a).…”
Section: Changes In Terrestrial Snow Packmentioning
confidence: 99%
“…In addition, the bright surface features or boundaries between water bodies and land can increase erroneous snow detection. These errors are eliminated using interactive techniques where multiple images were used along with microwave data [6].…”
Section: Introductionmentioning
confidence: 99%
“…IMS analysts use these multiple sources with different spatial resolution within the interactive multisensor snow and ice mapping system to re-gridded to map snow and sea ice extent in 4 km spatial resolution. The analyst begins charting using the map from the previous day, then uses the satellite inputs accordingly [6]. The daily IMS maps replaced weekly maps of snow and sea ice extent drawn by hand since 1966.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The NOAA-CDR SAE is computed from the gridded monthly snow cover databases, deriving from the NOAA weekly snow charts for 1966-1999(Robinson, 1993 and the Interactive Multi-Sensor (IMS) daily snow product for 1999 afterwards (Ramsay, 1998;Helfrich et al, 2007). The NOAA CDR SAE monthly time series averaged over NH are obtained from the Rutgers University (http://climate.rutgers.edu/snowcover/).…”
Section: Validation Datamentioning
confidence: 99%